PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE TERHADAP MAHĀRAH AL QIRĀAH DI MA’HAD ‘ALY NURUL JADID - Abidah, Aniqah Laili; Ulum, Moh. (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
The cooperative learning model known as Think Pair Share (TPS) emphasizes students' cooperation to help each other and discuss the Arabic text they will read. The purpose of this study was to find out how the learning model of TPS Ma'had Aly Nurul Jadid influenced the maha>arah al qira>ah in I'dadiyah students. This study used quantitative research techniques and survey types based on variable characteristics. The population of this study consisted of 140 Ma'had Aly Nurul Jadid students from Tamhidiyah, I'dadiyah, and Ma'had Aly programs. using a sample size of 25 students from I'dadiyah Ma'had Aly Nurul Jadid. The instruments used to collect data were questionnaires for the independent variable (x) and oral tests for the dependent variable (y). While the analysis technique based on the hypothesis is associative or correlative (cause or cause) and uses Somer's D method with the help of the SPSS 16.0 for Windows application, which uses ordinal data, Based on the results of the data analysis, the results showed no influence between the TPS Learning Model and maha>rah al qira>ah, as evidenced by Approx. Sig., which obtained a value of 0.171 > 0.05, then it was declared insignificant because the value was greater than the value of statistical provisions (criticism value), which was 0.05. So the TPS Learning Model has no influence on the maharah al qiraah.